Dronesourcing: a modular, expandable multi-sensor UAV platform for combined, real-time environmental monitoring. Issue 8 (19th May 2017) - Tripolitsiotis, Achilleas; Prokas, Nikolaos; Kyritsis, Sarantis; Dollas, Apostolos; Papaefstathiou, Ioannis; Partsinevelos, Panagiotis
ABSTRACT: The systematic environmental monitoring of the land, atmosphere, oceans and their coupling zones, is assisted by the use of unmanned aerial vehicles (UAVs) that can operate over rural and/or urban areas to provide enhanced spatial and temporal measurement resolutions compared against corresponding satellite products. The international UAV market includes a vast number of solutions that carry sensors for environmental monitoring varying in type, flight time, carrying weight, communication, and autonomous flight. The majority of these commercial UAVs (especially the low-cost ones) have been designed for specific applications and their main disadvantage is that they can only integrate the payload they have been initially designed to carry, thus presenting minimal modularity. This work presents a modular and affordable platform where the user can easily adapt almost any type of environmental monitoring sensor, which can transmit its measurements to the UAV flight controller without the need for any additional modification. A novel communication protocol has been developed that is also capable to incorporate proximity sensors for collision avoidance. In addition, a wireless mobile telecommunications module incorporation through the use of mobile devices on the UAV providesreal- time animated map generation along with cooperative capabilities for fleet missions.